2009
DOI: 10.1016/j.fgb.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and autophagy play a role in survival and differentiation of the phytopathogen Moniliophthora perniciosa

Abstract: The hemibiotrophic basidiomycete Moniliophthora perniciosa causes "witches' broom disease" in cacao (Theobroma cacao). During plant infection, M. perniciosa changes from mono to dikaryotic life form, an event which could be triggered by changes in plant nutritional offer and plant defense molecules, i.e., from high to low content of glycerol and hydrogen peroxide. We have recently shown that in vitro glycerol induces oxidative stress resistance in dikaryotic M. perniciosa. In order to understand under which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
1
15
0
2
Order By: Relevance
“…This data is in agreement with the stability of gfp silencing during growth described above and further supports the conclusion that silencing is maintained during long periods. Recently, Pungartnik et al (2009) demonstrated the effects of ROS in the M. perniciosa biology, thus, the silencing of MpPRX1 will be very important to validate several hypothesis raised in this work.…”
Section: Discussionsupporting
confidence: 60%
“…This data is in agreement with the stability of gfp silencing during growth described above and further supports the conclusion that silencing is maintained during long periods. Recently, Pungartnik et al (2009) demonstrated the effects of ROS in the M. perniciosa biology, thus, the silencing of MpPRX1 will be very important to validate several hypothesis raised in this work.…”
Section: Discussionsupporting
confidence: 60%
“…For instance, it will be important to determine how biotrophy is maintained for so long in M. perniciosa and how cacao senescence signals the end of this fungal stage. Given that nutrient availability and stress conditions seem to be tightly associated with M. perniciosa virulence and development (Alvim et al, 2009;Pungartnik et al, 2009;Thomazella et al, 2012;Argôlo Santos Carvalho et al, 2013), cacao nutritional status (e.g., carbon starvation) and/or specific plant molecules (e.g., ROS) possibly orchestrate WBD infection. It will be relevant to establish to what extent and how the alterations identified in cacao metabolism/physiology correlate with direct fungal action.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in-depth studies of this fungus have been published: M. perniciosa was found to produce hormones and alter endogenous auxin and salicylic acid levels in infected cocoa leaves (Kilaru et al, 2007), as well as necrosis-inducing proteins during infection, i.e., Mp-NeP1 and Mp-NeP2, which are differentially secreted during the course of infection in planta ; Rincones et al (2008) found that genes expressed in the biotrophic phase of M. perniciosa are under catabolite and nitrogen repression. Glycerol seems to play several roles in M. perniciosa biology; Santos et al (2008) showed that M. perniciosa's resistance to stress depends on glycerol, and Pungartnik et al (2009) showed that small amounts of hydrogen peroxide in glycerol medium induce the formation of clamp connections in vitro and that basidiospores are the most resistant life form of this fungus when compared to mono-and dikaryotic cells.…”
Section: Introductionmentioning
confidence: 99%